The effect of work-life balance, work environment, and workplace spiritually on work engagement - Asmawati, Nanda (Journal of Management and Business Insight, 2024)
Purpose-Employees are essential to running the operational process and achieving goals. Therefore, it is essential to pay attention to the factors that affect employee performance, especially their engagement at work. This study aims to analyze the influence of work-life balance, work environment, and spirituality in the workplace on work engagement. Design/Methodology/Approach-This study analyzes work engagement among employees of Amanah Anda Company located in Yogyakarta, Indonesia. Data was obtained from 87 employees using a questionnaire. Then, the research data was processed using SPSS software. Findings-This study found that work-life balance and spirituality in the workplace can have a positive effect on work engagement. Increasing work-life balance and workplace spirituality can increase employee work engagement. The work environment in this study proved not to affect work engagement, so the condition of the work environment does not affect employee work engagement at work. Research limitations/implications-This research is limited to Amanah Anda Company employees engaged in a self-service business venture in Yogyakarta, Indonesia. The results of this study cannot be used to generalize work engagement to all self-service businesses in Yogyakarta. Originality/value-This research focuses on employees of Amanah Anda Company, located in Yogyakarta, and similar research has never been done before. Other studies determining work engagement use different business models, so this research has never been done before.